Linking the Clinical Dementia Rating Scale-Sum of Boxes, the Clinician’s Interview-Based Impression Plus Caregiver Input, and the Clinical Global Impression Scale: evidence based on individual participant data from five randomized clinical trials of donepezil - Samara, M; Levine, SZ; Yoshida, K; Goldberg, Y; Cipriani, A; Efthimiou, O; Iwatsubo, T; Leucht, S; Furakawa, TA (IOS Press, 2021)
Background: In patients with Alzheimer’s disease, global assessment scales, such as the Clinical Dementia Rating-Sum of Boxes (CDR-SB), the Clinician’s Interview-Based Impression Plus Caregiver Input (CIBI plus), and the Clinical Global Impression (CGI) are commonly used. Objective: To clinically understand and interpret the associations between these scales, we examined the linkages for the total and change scores of CDR-SB, CIBI plus, and CGI. Methods: Individual participant data (N = 2,198) from five pivotal randomized placebo-controlled trials of donepezil were included. Data were collected at baseline and scheduled visits for up to 6 months. Spearman’s correlation coefficients ρ were examined between corresponding total and change scores of simultaneous CDR-SB, CIBI plus, and CGI ratings. To link between the simultaneous ratings, equipercentile linking was used. Results: We found strong evidence that the Spearman’s correlation coefficients between the CDR-SB and CGI, and CDR-SB and CIBI plus total scores were at least adequately correlated (ρ= 0.50 to 0.71, with p <  0.01). The correlation coefficients between the change scores of CDR-SB and CGI were deemed adequate for weeks 6 to 24 (ρ= 0.44 to 0.65); the remaining correlations were smaller in magnitude (ρ= 0.09 to 0.35). Overall, the linkages were in-line with expectations, e.g., CDR-SB range score of 3-4 (= very mild dementia) was linked to a CGI score of 3 (= mildly ill), and an increase of CDR-SB of 1 was linked to a change of 5 (= minimal worsening) in both CGI and CIBI plus. Conclusion: The study findings can be useful for clinicians wishing to compare scores of different scales across patients. They can also help researchers understand results of studies using different scales and can facilitate meta-analyses, to increase statistical power.